2005
DOI: 10.1038/sj.sc.3101854
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns of Japanese physicians in urologic surveillance and management of spinal cord injury patients

Abstract: Study design: Analysis of answers to a new questionnaire. Objective: To examine current practice patterns of physicians in the urological surveillance and management of spinal cord injury (SCI) patients in Japan. Setting: Nationwide questionnaire survey to physicians in Japan. Methods: A Japanese version of the 14-item questionnaire survey carried out in US was mailed to 770 members of the Japanese Neurogenic Bladder Society (JNBS). Results: We received answers to our questionnaire from 333 (43.2%) members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…The previous literature did not show consensus on the frequency of urodynamics requested by physicians. 2,3,5 The present study showed that only 12% of the Dutch urologists repeated routinely urodynamics. Furthermore, only 11% of the adult urologists perform video urodynamics, which is regarded as the golden standard by the EAU guidelines.…”
Section: This Is the First Survey Among Urologists On The Implementatmentioning
confidence: 88%
See 1 more Smart Citation
“…The previous literature did not show consensus on the frequency of urodynamics requested by physicians. 2,3,5 The present study showed that only 12% of the Dutch urologists repeated routinely urodynamics. Furthermore, only 11% of the adult urologists perform video urodynamics, which is regarded as the golden standard by the EAU guidelines.…”
Section: This Is the First Survey Among Urologists On The Implementatmentioning
confidence: 88%
“…Available studies surveyed physicians involved in the treatment of SCI only. [2][3][4] For example, Bycroft et al 3 surveyed consultant urologists in spinal injuries units in the UK and Ireland on different aspects of neurogenic bladder dysfunction. They did not find any consensus on the frequency of visits, protocols for urinary tract infections and the need of routine urodynamics.…”
Section: Introductionmentioning
confidence: 98%
“…Given the aggressive bladder tumors that can present in SCI patients, cystoscopies may not occur at a time to significantly influence management. Despite this, 95% of Japanese urologists believe in annual cystoscopy for SCI patients, 39 and an American survey found that 25% of urologists perform routine cystoscopy on all SCI patients whereas 75% perform yearly cystoscopy if the patient uses an indwelling catheter. 40 To date, guidelines have not recommended specific strategies to mitigate the morbidity and mortality associated with bladder cancer.…”
Section: Risk Factors For Development Of Bladder Cancer In Sci Patientsmentioning
confidence: 99%
“…8 Others have advocated screening SCI patients with an indwelling catheter after 8-10 years of use with yearly cystoscopy, cytology, and possible biopsy. 9 11 show that the majority of urologists are performing annual cystoscopies for patients with long-term indwelling catheters, and 75-88% perform them if the patient has an indication such as hematuria or bladder stones. There has also been some interest in the use of urine tumor markers for screening.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these findings have been noted in earlier studies. 3,11,[13][14][15][16] The reason for the rapid and aggressive nature of these tumors is unknown. In other populations with bladder cancer, approximately 25% will present with muscle invasive disease, 6 whereas in this study over 1/2 had advanced disease at presentation.…”
Section: Discussionmentioning
confidence: 99%